(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This study examines the role of sustainable economic development models in reducing poverty at the regional level. It explores the theoretical foundations of poverty reduction and analyzes practical approaches that promote inclusive economic growth, employment generation, social protection, financial inclusion, and institutional development. The research highlights the importance of integrating economic, social, and environmental dimensions of development to ensure long-term poverty alleviation. Particular attention is given to regional development strategies that enhance human capital, improve infrastructure, and create opportunities for vulnerable populations. The findings suggest that sustainable economic development models contribute significantly to improving living standards, reducing income disparities, and strengthening regional economic resilience.